2019
DOI: 10.1101/831883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic encryption of digital data stored in synthetic DNA

Abstract: Today, we can read human genomes and store digital data robustly in synthetic DNA.Here we report a strategy to intertwine these two technologies to enable the secure storage of valuable information in synthetic DNA, protected with personalized keys. We show that genetic short tandem repeats (STRs) contain sufficient entropy to generate strong encryption keys, and that only one technology, DNA sequencing, is required to simultaneously read key and data. Using this approach, we experimentally generated 80 bit st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In (7), Iter and t max , respectively, represent the current number of iterations and the maximum number of iterations, and α 2 is the fixed value to control the development capacity. In addition, parameter α 1 is used to enhance the diversity and exploration capability of the population, as follows:…”
Section: A Equilibrium Optimizermentioning
confidence: 99%
See 1 more Smart Citation
“…In (7), Iter and t max , respectively, represent the current number of iterations and the maximum number of iterations, and α 2 is the fixed value to control the development capacity. In addition, parameter α 1 is used to enhance the diversity and exploration capability of the population, as follows:…”
Section: A Equilibrium Optimizermentioning
confidence: 99%
“…Their experiments proved that ddPCR is an effective method for detecting DNA storage. In addition, Grass et al [7] reported a strategy of using personal genetic information to securely store valuable information in synthetic DNA based on security considerations as well as using personal genetic information to personalize key protection. In 2020, Meiser [8] released a DNA storage experiment program, providing steps and precise instructions for converting digital information into DNA sequences and then regaining the information through DNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…DNA is a promising medium for archival data because of its superior storage density and longevity. 1,2 It can also be selectively accessed, queried like a database, and even operated on like a parallel computer. [3][4][5] Finally, whereas conventional archival media are consistently at the risk of becoming unreadable in the future due to both planned and unintended obsolescence, DNA is guaranteed to remain readable.…”
Section: Introductionmentioning
confidence: 99%